The effect of social power dimension on repurchase intention with economic satisfaction as mediation - Fadel Hussen; Gesit Thabrani; Husnil Khatimah (Jurnal Kajian Manajemen dan Wirausaha, 2022)
This study aims to analyze the effect of expert power and referent power on repurchase intention with economic satisfaction as a mediation to consumers of Erigo products in West Sumatra. The population in this study are consumers who have bought Erigo products and user of social media Instagram.The number of samples in this study were 240 respondents. Data was collected through the distribution of online questionnaires and data processing was carried out through SmartPLS software. The results of this study indicate that (1) Expert Power has a positive and significant effect on Economic Satisfaction, (2) Referent Power has a positive and significant effect on Economic Satisfaction, (3) Economic Satisfaction has a positive and significant effect on Repurchase Intention, (4) Expert Power has an effect on positive and significant impact on Repurchase Intention with Economic Satisfaction as mediation, (5) Referent Power has a positive and significant effect on Repurchase Intention with Economic Satisfaction as mediation.